Aluminum foil for battery as well as preparation method and application of aluminum foil

By adding rare earth elements to aluminum foil and adopting a multi -stage annealing process to refine the grains of aluminum foil, the problem of existing aluminum foil grain size and electrochemical properties have been solved, and the performance of aluminum foil is achieved. Battery.

CN119372510APending Publication Date: 2025-01-28YUNNAN HAOXIN ALUMINUM FOIL

Patent Information

Application Number
CN202411460783.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing aluminum foil has a large grain size, which affects its mechanical properties and electrochemical properties and hinders its application in lithium-ion batteries.

Method used

By adding rare earth elements to the chemical ingredients of aluminum foil, and combined with multi -stage annealing process, refine the grains of aluminum foil. The addition of rare earth elements such as y (y) and 铪 (HF) can refine the grains. Multi -stage annealing can further refine the grains by adjusting the micro structure and eliminating stress.

Benefits of technology

Significantly improve the strength, toughness, plasticity, processing performance, corrosion resistance and electrical resistance of aluminum foil, and meet the performance requirements of lithium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091808190000071
    Figure BDA0005091808190000071
  • Figure BDA0005091808190000072
    Figure BDA0005091808190000072
  • Figure BDA0005091808190000101
    Figure BDA0005091808190000101
Patent Text Reader

Abstract

The invention belongs to the technical field of metal aluminum, and provides an aluminum foil for a battery as well as a preparation method and application thereof. The method comprises the following steps that S1, a blank with rare earth elements is obtained through smelting; s2, the blank is cast-rolled and coiled, and an aluminum coiled material is obtained; s3, the aluminum coiled material is subjected to multi-pass cold rolling, and a cold-rolled aluminum strip is obtained; s4, the cold-rolled aluminum strip is subjected to multi-stage annealing, and an annealed aluminum strip is obtained; and S5, the annealed aluminum strip is subjected to multi-pass finish rolling, and the aluminum foil for the battery is obtained. Rare earth elements are added into chemical components of the aluminum foil, a multi-stage annealing process is combined, and grains can be refined through a synergistic effect. Therefore, the mechanical property and the electrochemical property of the aluminum foil are improved, and application of the aluminum foil in lithium ion batteries is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal aluminum, and in particular, relates to an aluminum foil for battery and a preparation method and application thereof. Background Art

[0002] Aluminum foil is a metal sheet material with aluminum as the main material, which is processed through multiple rolling processes to a thickness of less than 0.2 mm. Its thickness usually ranges from 0.006 mm to 0.2 mm. Aluminum foil has excellent electrical conductivity, outstanding barrier properties, good light-shielding properties, excellent ductility and plasticity, light weight and corrosion resistance, non-toxic and odorless, hygienic and safe, good thermal conductivity, recyclability and environmental protection, and other excellent properties. It is widely used in many fields.

[0003] Aluminum foil for batteries is mainly used as a positive electrode collector for lithium-ion batteries, responsible for collecting the current generated by the positive electrode and transmitting it to the external circuit. However, the grain size of aluminum foil prepared by the prior art is relatively large, which will have an adverse effect on its mechanical properties and electrochemical properties, thereby hindering its application in lithium-ion batteries. Chinese patent CN118621188A discloses an aluminum alloy material for aluminum foil blanks, a preparation method and application thereof, which realizes the composite modification of 1235D aluminum alloy by adding a specific proportion of rare earth element Sc and chemical element Zr to the alloy composition of 1235D aluminum alloy, achieving the effect of grain refinement by reducing the grain size, but the price of its rare earth element Sc is relatively expensive. Chinese patent CN117604299A discloses a battery aluminum foil and its preparation method. The prepared battery aluminum foil has a thickness of 0.01-0.015 mm, a tensile strength greater than 250 MPa, an elongation greater than 5%, and a surface appearance without color difference and bright line defects, and ensures a flat plate shape with a collapse amount of less than 4 mm, thereby meeting the performance improvement requirements of the positive electrode current collector aluminum foil. However, its preparation method is relatively cumbersome, and the conductivity of the aluminum foil is poor. Therefore, based on the above description, it is urgent to develop a method that can refine the grain size of the aluminum foil, thereby improving the mechanical properties and electrochemical properties of the aluminum foil. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to refine the grain size of the aluminum foil, thereby improving the mechanical properties and electrochemical properties of the aluminum foil, which is beneficial to the application of the aluminum foil in lithium-ion batteries.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing aluminum foil for a battery comprises the following steps:

[0007] S1. Obtaining a blank containing rare earth elements by smelting;

[0008] S2, casting and coiling the billet to obtain an aluminum coil;

[0009] S3, cold-rolling the aluminum coil for multiple passes to obtain a cold-rolled aluminum strip;

[0010] S4, performing multi-stage annealing on the cold-rolled aluminum strip to obtain an annealed aluminum strip;

[0011] S5, performing multiple passes of finish rolling on the annealed aluminum strip to obtain aluminum foil for batteries.

[0012] The present invention adds rare earth elements to the chemical composition of the aluminum foil and combines it with a multi-stage annealing process, which can synergistically refine the grains.

[0013] The effects of rare earth elements include: (1) Grain refinement: When rare earth elements are added to aluminum foil, because their atomic radius is larger than that of aluminum atoms, they can fill the surface defects of the alloy phase in the aluminum melt, reduce the surface tension at the interface between the new and old phases, thereby accelerating the formation of crystal nuclei and inhibiting the growth of grains. This grain refinement effect helps to improve the mechanical properties, corrosion resistance and processing properties of aluminum foil. (2) Microalloying effect: Rare earth elements can also form compounds with aluminum. These compounds act as external crystal nuclei when the metal liquid crystallizes, increase the number of crystal nuclei, and further refine the grains. (3) Dehydrogenation, refining, and purification effects: Rare earth elements have a strong affinity with gases such as hydrogen and many non-metals, and can generate compounds with high melting points, which help to remove impurities and gases in aluminum foil and improve the purity of aluminum foil.

[0014] The effects of multi-stage annealing include: (1) Adjusting the microstructure: Multi-stage annealing can gradually adjust the microstructure of aluminum foil by performing heat preservation treatment at different temperatures, making it more uniform and stable. (2) Relieving stress: During the annealing process, the stress inside the aluminum foil will gradually release, which is conducive to reducing cracks and fractures caused by stress concentration. (3) Promoting phase transformation: At a specific annealing temperature, certain phases in the aluminum foil will undergo transformations, and these phase transformations help to refine the grains or improve the grain morphology.

[0015] When rare earth elements are added to aluminum foil and combined with a multi-stage annealing process, the two can produce a synergistic effect to further refine the grains. The addition of rare earth elements provides more nucleation points for aluminum foil, accelerates the formation of crystal nuclei and inhibits the growth of grains. The multi-stage annealing process promotes the uniform distribution and phase change process of rare earth elements in aluminum foil by adjusting the annealing temperature and holding time, thereby further refining the grains.

[0016] Furthermore, the chemical components of the blank include: Si, Fe, Cu, Mn, Mg, Ti, Al, Y and Hf.

[0017] Furthermore, based on the mass fraction of the aluminum foil for the battery, the content of Y is 0.04-0.1%, and the content of Hf is 0.02-0.05%.

[0018] Y (yttrium): In aluminum foil blanks, the content of Y is controlled between 0.04% and 0.1%. The synergistic effect of Y and Hf (hafnium) can significantly refine the grains and improve the material's organizational structure, thereby improving the material's mechanical properties and processing properties. In addition, Y also helps remove inclusions in aluminum melt and improve the purity of aluminum foil.

[0019] Hf (Hafnium): The content of Hf in aluminum foil is controlled between 0.02% and 0.05%. Similar to Y element, Hf also has the effect of refining grains and can further improve the performance of the material. At the same time, the addition of Hf can also improve the corrosion resistance and heat resistance of aluminum foil.

[0020] Further, in step S5, the multi-stage annealing includes the following steps:

[0021] S51, performing a first stage annealing on the cold-rolled aluminum strip under a first set condition;

[0022] S52, performing a second stage annealing on the cold-rolled aluminum strip after the first stage annealing under a second set condition;

[0023] S53, performing a third stage annealing under a third set condition on the cold-rolled aluminum strip after the second stage annealing;

[0024] S54, air-cooling the cold-rolled aluminum strip after the third stage annealing to room temperature.

[0025] Furthermore, the first setting conditions include: a heating rate of 3 to 5°C / s, a heating temperature of 200 to 250°C, and a heat preservation time of 10 to 30 minutes.

[0026] Furthermore, the second setting conditions include: a heating rate of 1 to 3°C / s, a heating temperature of 300 to 330°C, and a heat preservation time of 180 min to 600 min.

[0027] Furthermore, the third setting condition includes: a heating rate of 1 to 3°C / s, a heating temperature of 350 to 400°C, and a holding time of 10 to 30 minutes.

[0028] In the annealing process of aluminum foil production, multi-stage annealing is an important step, which helps to eliminate the residual stress generated during cold rolling, refine the grains, improve the processing properties of the material and the performance of the final product. S51 The purpose of the first stage annealing: to preliminarily eliminate the residual stress generated during cold rolling and prepare for the subsequent annealing stage. Heating rate: 3-5℃ / s. This moderate heating rate can not only ensure the uniformity of annealing, but also avoid the uneven structure caused by too fast heating. Heating temperature: 200-250℃. This temperature range is relatively low, which helps to preliminarily soften the material without causing excessive recrystallization. Holding time: 10-30min to ensure that stress is fully released. S52 The purpose of the second stage annealing: to further eliminate residual stress, promote recrystallization, and refine the grains. Heating rate: 1-3℃ / s. Compared with the first stage, the heating rate is reduced to reduce the temperature gradient inside the material and promote uniform annealing. Heating temperature: 300-330℃. Higher temperatures help accelerate the recrystallization process and refine the grains. Holding time: 180min~600min. Longer holding time ensures sufficient recrystallization and grain refinement process, thereby improving the mechanical properties of the material. S53 Third stage annealing purpose: stabilize the material structure and adjust the final performance of the material. Heating rate: the same as the second stage, 1~3℃ / s. Heating temperature: 350~400℃. This temperature range helps to further stabilize the material structure and can improve the material performance by precipitation strengthening and other methods. Holding time: 10~30min. Although the holding time is relatively short, at this high temperature, the material is close to its final performance state, so there is no need for too long holding time. S54 Air cooling to room temperature purpose: cool the annealed aluminum foil naturally to room temperature to avoid introducing new residual stresses due to rapid cooling. Process: place the aluminum foil after the third stage annealing in the air to cool naturally to room temperature.

[0029] The second object of the present invention is to provide an aluminum foil obtained by the method for preparing aluminum foil for batteries described in any one of the embodiments of the first object, wherein the average grain size of the aluminum foil is 3 to 8 μm.

[0030] Furthermore, the aluminum foil satisfies at least one of the following properties: tensile strength of 250-280 MPa, elongation ≥5%, thermal conductivity of 220-250 W / (m˙K), and electrical conductivity of 70-90 s / m.

[0031] The third object of the present invention is to provide a lithium ion battery, wherein the lithium ion battery comprises the aluminum foil described in the embodiment of the second object.

[0032] The beneficial effects of the present invention are:

[0033] (1) Refining the grain size of aluminum foil can significantly improve the strength, toughness, plasticity, processing performance, corrosion resistance and conductivity of aluminum foil. The tensile strength of aluminum foil is 250-280 MPa, the elongation is ≥5%, the thermal conductivity is 220-250 W / (m˙K), and the electrical conductivity is 70-90 s / m.

[0034] (2) The addition of rare earth elements and subsequent multi-stage annealing treatment help refine the grains of aluminum foil, thereby enhancing the strength and toughness of aluminum foil. Grain refinement can increase the number of grain boundaries per unit volume, which have an obstructive effect on dislocation movement, thereby increasing the yield strength and tensile strength of the material. At the same time, fine grains also help to improve the toughness of the material, reduce the path of crack propagation, and improve the fracture resistance.

[0035] (3) Grain refinement can also improve the corrosion resistance of aluminum foil, because the increase in grain boundaries shortens the diffusion path of the corrosive medium inside the aluminum foil and reduces the corrosion rate. This is especially important for aluminum foil used in batteries, because batteries may be affected by various corrosive environments during use.

[0036] (4) Multiple cold rolling and multiple finishing rolling can gradually improve the processing performance of aluminum foil, making it more uniform and stable. The cold rolling process can remove some defects in the casting and rolling process, such as segregation and pores, and make the thickness and performance of the aluminum foil more uniform. The finishing rolling process further improves the surface quality and dimensional accuracy of the aluminum foil to meet the strict requirements of battery manufacturing. Multi-stage annealing can more effectively eliminate the residual stress generated during the cold rolling process and make the structure of the aluminum foil more stable. At the same time, by precisely controlling the annealing temperature and holding time, the mechanical properties of the aluminum foil can be optimized, making it more suitable as a battery material. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0038] Example 1

[0039] This embodiment provides a method for preparing aluminum foil for a battery, comprising the following steps:

[0040] S1. A blank containing rare earth elements is obtained by batching (cold material (ingot) + master alloy), furnace charging, smelting, refining, and solution purification. The chemical composition of the blank is shown in Table 1.

[0041] S2, casting and rolling the billet (6.4 mm) and coiling to obtain an aluminum coil; the production process parameters of casting and rolling are: the front box temperature is 700° C., the cooling water temperature is 42° C., the thickness of the casting and rolling zone is 60 mm, and the strip speed is 1100 mm / min;

[0042] S3, cold rolling the aluminum coil for multiple passes to obtain a cold-rolled aluminum strip; the production process of multiple cold rolling (rolling the cast-rolled 6.4 mm coil to 0.24 mm according to the following rolling process) includes: cold rolling → annealing → cold rolling → re-coiling (trimming) → cold rolling (intermediate cooling) → longitudinal cutting → inspection. The production parameters of multiple cold rolling are shown in Table 2;

[0043] S4, performing multi-stage annealing on the cold-rolled aluminum strip to obtain an annealed aluminum strip; the production parameters of the multi-stage annealing are shown in Table 3;

[0044] S5. The annealed aluminum strip is subjected to multiple passes of finish rolling to obtain aluminum foil for batteries. The production process of multiple passes of finish rolling (rolling the cold-rolled sheet with a thickness of 0.24 mm to a finished product thickness of 0.012 / 0.013) is: intermediate rolling 1 pass → intermediate rolling 2 passes → intermediate rolling 3 passes → finish rolling → material inspection (others) → coiling → inspection → packaging. The production parameters of multiple passes of finish rolling are shown in Table 4.

[0045] Table 1 Chemical composition of the blank

[0046] Components Si Fe Cu Mn Mg Ti Y Hf Mass fraction (%) 0.04 0.22 0.04 0.01 0.002 0.02 0.04% 0.05%

[0047] The remaining elements in Table 1 are Al (Al content>99.5%) and unavoidable impurities (total content of P and S≤0.009%).

[0048] Table 2 Production parameters of multi-pass cold rolling

[0049]

[0050] Table 3 Production parameters of multi-stage annealing

[0051] Annealing stage Heating rate (℃ / s) Heating temperature(℃) Holding time (min) Phase 1 4 200 20 Phase II 2 300 600 Phase 3 2 350 20

[0052] Table 4 Production parameters of multi-pass finishing rolling

[0053]

[0054] Example 2

[0055] The difference between Example 2 and Example 1 is that the chemical composition of the blank is shown in Table 5.

[0056] Table 5 Chemical composition of the blank

[0057] Components Si Fe Cu Mn Mg Ti Y Hf Mass fraction (%) 0.04 0.22 0.04 0.01 0.002 0.02 0.1% 0.02%

[0058] The remaining elements in Table 5 are Al (Al content>99.5%) and unavoidable impurities (total content of P and S≤0.009%).

[0059] Example 3

[0060] The difference between Example 3 and Example 1 is that the chemical composition of the blank is shown in Table 6.

[0061] Table 6 Chemical composition of the blank

[0062] Components Si Fe Cu Mn Mg Ti Y Hf Mass fraction (%) 0.04 0.22 0.04 0.01 0.002 0.02 0.07% 0.035%

[0063] The remaining elements in Table 6 are Al (Al content>99.5%) and unavoidable impurities (total content of P and S≤0.009%).

[0064] Example 4

[0065] The difference between Example 4 and Example 1 is that the production parameters of the multi-stage annealing are shown in Table 7.

[0066] Table 7 Production parameters of multi-stage annealing

[0067] Annealing stage Heating rate (℃ / s) Heating temperature(℃) Holding time (min) Phase 1 5 250 10 Phase II 3 330 300 Phase 3 3 400 10

[0068] Comparative Example 1

[0069] The difference between Comparative Example 1 and Example 1 is that the chemical composition of the blank is as shown in Table 8.

[0070] Table 8 Chemical composition of the blank

[0071] Components Si Fe Cu Mn Mg Ti Y Mass fraction (%) 0.04 0.22 0.04 0.01 0.002 0.02 0.09%

[0072] The remaining elements in Table 8 are Al (Al content>99.5%) and unavoidable impurities (total content of P and S≤0.009%).

[0073] Comparative Example 2

[0074] The difference between Comparative Example 2 and Example 1 is that the chemical composition of the blank is shown in Table 9.

[0075] Table 9 Chemical composition of the blank

[0076] Components Si Fe Cu Mn Mg Ti Hf Mass fraction (%) 0.04 0.22 0.04 0.01 0.002 0.02 0.09%

[0077] The remaining elements in Table 9 are Al (Al content>99.5%) and unavoidable impurities (total content of P and S≤0.009%).

[0078] Comparative Example 3

[0079] The difference between Comparative Example 3 and Example 1 is that the annealing production parameters are: heating temperature is 320° C., holding time is 4 h, and then air cooling to room temperature.

[0080] Test example

[0081] The aluminum foils obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were tested for grain size, tensile strength, elongation, thermal conductivity and electrical conductivity, and the results are shown in Table 10. The grain size was determined by the straight line intercept method combined with professional image analysis software (Image-ProPlus); the tensile strength and elongation were determined by the method of national standard GB / T 2884; the thermal conductivity was determined by the heat flow meter method; and the electrical conductivity was determined by the national standard GB / T 3190-2008 "Chemical Analysis Methods for Aluminum and Aluminum Alloys".

[0082] Table 10 Performance results of aluminum foil

[0083]

[0084]

[0085] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing aluminum foil for battery, characterized in that: The following steps are involved: S1. Obtaining a blank containing rare earth elements by smelting; S2, casting and coiling the billet to obtain an aluminum coil; S3, cold-rolling the aluminum coil for multiple passes to obtain a cold-rolled aluminum strip; S4, performing multi-stage annealing on the cold-rolled aluminum strip to obtain an annealed aluminum strip; S5, performing multiple passes of finish rolling on the annealed aluminum strip to obtain aluminum foil for batteries.

2. The method for preparing aluminum foil for battery according to claim 1, characterized in that: The chemical components of the blank include: Si, Fe, Cu, Mn, Mg, Ti, Al, Y and Hf.

3. The method for preparing aluminum foil for battery according to claim 2, characterized in that: Calculated by mass fraction of the aluminum foil for batteries, the content of Y is 0.04-0.1%, and the content of Hf is 0.02-0.05%.

4. The method for preparing aluminum foil for battery according to claim 1, characterized in that: In step S5, the multi-stage annealing comprises the following steps: S51, performing a first stage annealing on the cold-rolled aluminum strip under a first set condition; S52, performing a second stage annealing on the cold-rolled aluminum strip after the first stage annealing under a second set condition; S53, performing a third stage annealing under a third set condition on the cold-rolled aluminum strip after the second stage annealing; S54, air-cooling the cold-rolled aluminum strip after the third stage annealing to room temperature.

5. The method for preparing aluminum foil for battery according to claim 4, characterized in that: The first setting conditions include: a heating rate of 3 to 5°C / s, a heating temperature of 200 to 250°C, and a heat preservation time of 10 to 30 minutes.

6. The method for preparing aluminum foil for battery according to claim 4, characterized in that: The second setting conditions include: a heating rate of 1 to 3°C / s, a heating temperature of 300 to 330°C, and a heat preservation time of 180 min to 600 min.

7. The method for preparing aluminum foil for battery according to claim 4, characterized in that: The third setting conditions include: a heating rate of 1 to 3°C / s, a heating temperature of 350 to 400°C, and a heat preservation time of 10 to 30 minutes.

8. An aluminum foil obtained by the method for preparing aluminum foil for battery according to claims 1 to 7, characterized in that: The average grain size of the aluminum foil is 3 to 8 μm.

9. The aluminum foil according to claim 8, characterized in that The aluminum foil meets at least one of the following properties: tensile strength of 250-280 MPa, elongation ≥5%, thermal conductivity of 220-250 W / (m˙K), and electrical conductivity of 70-90 s / m.

10. A lithium ion battery, characterized in that: The lithium ion battery comprises the aluminum foil as claimed in claim 8 or 9.

Citation Information

Patent Citations

  • Battery aluminum foil and preparation method thereof

    CN117604299A

  • Aluminum alloy material for aluminum foil blank as well as preparation method and application of aluminum alloy material

    CN118621188A

Cited By

  • Soft package aluminum foil for power lithium battery and production method of soft package aluminum foil

    CN120575076A